Low Level of Haptoglobin in Lupus. (January 2017) - Timlin, Homa; Machireddy, Kirthi; Petri, Michelle
Haptoglobin levels are measured in systematic lupus erythematosus patients as part of the workup for anemia, with low levels indicating hemolysis. Haptoglobin is an acute phase protein. We present 2 lupus patients who were found to have low haptoglobin levels in the absence of other evidence of hemolysis.